Caribbean Report 08-08-1988 - Whitehorne, Pat (anchor); Hamid, Rizu (correspondent); Greenidge, Carl (interviewee); Crosskill, Hugh (correspondent); Richards, Steve (correspondent); Roach, Larry (interviewee); Pascal, Alex (interviewee) (The British Broadcasting Corporation, 1988)
This program features a report on a demonstration by Surinamese nationals at the French consulate in Holland in a bid to influence an end to French support for the rebel movement based in French Guiana. It also highlights an interview with Guyana’s Foreign Minister Carl Greenidge who speaks about his efforts to secure financial assistance for Guyana in Europe. The program also reports on some concerns involving public safety in the run up to Britain’s Notting Hill Carnival celebrations. Finally, the program takes a look at the recently concluded test series between the West Indies and England, which ended in a four nil victory for the visiting West Indies team.
1. Headlines: (Pat Whitehorn) (00:00-00:24)
2. Surinamese demonstrators at the French Consulate in Holland call for an end to support for Surinam’s rebel movement based in French Guiana. (BBC correspondent Rizu Hamid reports) (00:31-03:51)
3. Guyana’s Finance Minister Carl Greenidge wraps up European tour geared towards balance of payments assistance and export credits for Guyana. Pat Whitehorn interviews the Minister, who notes that no agreement has been reached with the IMF regarding economic measures appropriate for Guyana. (03:55-07:13)
4. Financial News: (Hugh Crosskill) (07:24-08:09)
Keywords: Carnival -- England.; Cricket --Tournaments -- England.; Cricket--Test matches--England.; Demonstrations -- Holland.; Military assistance, French.; Carnival -- Notting Hill.